Activities Of Lead And Zinc Oxides In CaO-SiO2-FeOX-AlO1.5 Slag - Katsunori Yamaguchi (The Minerals, Metals and Materials Society, 2006)
The zinc, lead and alumina contents in copper smelting slag are increasing with the increase in waste recycling. The recovery of base metals such as lead and zinc from copper converter slag is important from both an economical and environmental perspective. As a fundamental study of the metal recovery by reduction process, activity coefficients of ZnO and PbO in the CaO-SiO2-FeOx-5mass%AlO1.5 slag under iron saturation at 1573K are derived from the data of slag-metal equilibrium experiments. On the basis of the obtained data, the activity coefficients of ZnO and PbO in the CaO-SiO2-FeOx-5mass%AlO1.5 slag were compared with those of the CaO-SiO2-FeOx ternary system. Addition of alumina increases activities coefficient of ZnO and PbO in SiO2 rich side of the slag, and decreases them in CaO rich side.